Uncharted territory: the arrival of Psychoda albipennis (Zetterstedt, 1850) (Diptera: Psychodidae) in Maritime Antarctica - Hernandez-Martelo, Jordan; Contador, Tamara; Kim, Sanghee; Salina, Carla; Maturana, Claudia S.; Suazo, Manuel; Convey, Peter; Benítez, Hugo A. (Frontiers in Insect Science, 2024)
Despite increasing awareness of the threats they pose, exotic species continue to arrive in Antarctica with anthropogenic assistance, some of which inevitably have the potential to become aggressively invasive. Here, we provide the first report of the globally cosmopolitan species Psychoda albipennis (Diptera, Psychodidae; commonly known as moth flies) in Antarctica during the austral summer of 2021/2022, with the identification confirmed using traditional taxonomic and molecular approaches. The species was present in very large numbers and, although predominantly associated with the drainage and wastewater systems of Antarctic national operator stations in synanthropic situations, it was also present in surrounding natural habitats. While it is unclear if P. albipennis is capable of long-distance dispersal, adult psychodid flies are known to travel more than 90 m from their emergence sites, and up to 1.5 km with wind assistance. Thus, once established in the natural environment of King George Island there appears to be a high risk of the species rapidly becoming invasive. The introduction of non-native species such as P. albipennis can be a significant driver of future biodiversity change and loss, and seriously impact ecosystem health. In vulnerable low diversity ecosystems, such as in the terrestrial environments of Antarctica, non-native species can lead to step changes in ecological functions and interactions, displace native species and, potentially, lead to the extinction of native biota.